2014
DOI: 10.1371/journal.pntd.0003228
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Insecticide-Treated Nets, Curtains and Screening on Vector Borne Diseases, Excluding Malaria: A Systematic Review and Meta-analysis

Abstract: IntroductionInsecticide-treated nets (ITNs) are one of the main interventions used for malaria control. However, these nets may also be effective against other vector borne diseases (VBDs). We conducted a systematic review and meta-analysis to estimate the efficacy of ITNs, insecticide-treated curtains (ITCs) and insecticide-treated house screening (ITS) against Chagas disease, cutaneous and visceral leishmaniasis, dengue, human African trypanosomiasis, Japanese encephalitis, lymphatic filariasis and onchocerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 59 publications
0
68
0
Order By: Relevance
“…Based on our experience systematically reviewing the literature [16][17][18][19][20], we have identified repeated problems with vector control studies. To advance evidence-based policy making, the quality of evidence on vector control interventions -specifically the Malaria incidence House screening Socio-economic status (conf ounder)…”
mentioning
confidence: 99%
“…Based on our experience systematically reviewing the literature [16][17][18][19][20], we have identified repeated problems with vector control studies. To advance evidence-based policy making, the quality of evidence on vector control interventions -specifically the Malaria incidence House screening Socio-economic status (conf ounder)…”
mentioning
confidence: 99%
“…All eight reviews [1623] reported on the effects of chemical control on entomological indices and 4/8 [1618, 22] on dengue incidence. Chemical control included insecticide spraying, insecticide treated curtains, nets and screens, and larvicide application (particularly temephos).…”
Section: Resultsmentioning
confidence: 99%
“…Wilson and colleagues reviewed the effect of insecticide treated nets (1 study), curtains (3 studies) and screens (1 study) on entomological indices and of insecticide treated screens on dengue seroconversion [22]. Four studies had contemporary control groups (RCTs) and one was pre-post design.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review and meta-analysis identified clear evidence that ITNs have the potential to reduce pathogen transmission and morbidity from a vectorborne disease where vectors enter a house [12]. However, the use of ITNs is related to many factors.…”
Section: Discussionmentioning
confidence: 99%
“…There is also no established surveillance system in place [8]. Therefore, insecticide-treated bednets (ITNs) are one of the most effective methods to prevent mosquito-borne zoonotic disease including JE [10][11][12][13] in this country. Previous research studies identified several factors related to the use of ITNs: these include socio-demographic factors, availability of bed nets, knowledge, and attitudes towards mosquito-borne diseases [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%